Dynamic adaptive capacity of metalworking companies in Barranquilla - Colombia: analysis from the export process in the 4.0 Era (2023)
This article presents a methodology for analyzing the Dynamic Adaptive Capacity in the Export Process of metal-mechanical Small and medium-sized enterprises (SMEs) in Barranquilla - Colombia. In the new environments that are being developed in the 21st century, companies in different sectors have had the need to implement mechanisms that allow them to be able to face the constant changes that exist in the environment, especially in the 4.0 era. For its development, research of a documentary nature is proposed, which aims through the reports presented by four key informants that are part of 4 SMEs of the metal-mechanic sector in the city of Barranquilla, Colombia and are in charge of the export process. This establishes the following categories of analysis: strategic flexibility, intellectual flexibility, digital governance, leadership in virtual environments, technological resources and resilience. Due to this study, it was possible to recognize that based on the results of the qualitative analysis of the six dimensions of dynamic adaptive capacities (strategic flexibility, intellectual flexibility, resilience, leadership, resources and governance), a content analysis can be established, making possible to filter the main qualitative categories associated with flexibility, exporting, international, capacity, dynamics, adaptation, leadership, innovation, organization, resources, solutions, strategic, markets and SMEs.